2018
DOI: 10.2147/cmar.s182996
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RALY promotes migration and predicts poor prognosis in hepatocellular carcinoma

Abstract: IntroductionRALY plays a critical role in promoting invasiveness and is associated with poor prognosis in different types of cancers. However, the prognostic value of RALY and its precise role in hepatocellular carcinoma (HCC) remain unknown.Materials and methodsWe detected the expression of RALY in 127 clinical HCC tissue samples and seven HCC cell lines by immunohistochemical staining and Western blotting. The prognostic value of RALY expression was assessed using the Kaplan–Meier method. The expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The oncogenic role and regulatory effects have been reported in human cancers. Recent study indicated that overexpression of RALY predicted poor prognosis and acted as an oncogene in hepatocellular carcinoma (Zhu et al, 2018). In addition, RALY acted as a RNA binding protein to modulate metastatic potential of breast cancer cells (Bondy-Chorney et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role and regulatory effects have been reported in human cancers. Recent study indicated that overexpression of RALY predicted poor prognosis and acted as an oncogene in hepatocellular carcinoma (Zhu et al, 2018). In addition, RALY acted as a RNA binding protein to modulate metastatic potential of breast cancer cells (Bondy-Chorney et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…After searching protein-protein interaction database of STRING (https://string-db.org/), we found that RALYL could interact with multiple proteins, like TIGD3, RALY, RBM22, HNRNPCL1, HNRNPCL2, HNRNPC, CRNKL1, OR52N5, PNN and PPIE. RALY was up-regulated in multiple cancers, and RALY over-expression led to an aggressive biological behavior and a dismal prognosis as well as activating CDH1 signaling pathway [18][19][20]. By specific binding with RALY, RALYL could inhibit the oncogenic effects of RALY.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in tumorigenesis and development remains unclear. However, it has been reported as an oncogene in hepatocellular carcinoma 35 , clear cell renal cell carcinoma 36 , triple-negative breast cancer 37 , and non-small-cell lung cancer 38 . TSTA3, also known as GFUS, participates in the pathway of transporting to the Golgi apparatus as well as metabolism 39 , and is considered an oncogene in many cancers including esophageal squamous cell carcinoma 40 .…”
Section: Discussionmentioning
confidence: 99%